L’expertise stratégique face aux développements de l’intelligence articielle - Noyer, Jean-Max (Études internationales, 1988)
In the first section of this paper, the author tries to demonstrate how the increasing importance of modelisation/simulation reveals the existence of a crisis in strategic thought, seen as a crisis in the management of complexity, even more so as a crisis regarding the fundamental concepts of strategy, and regarding its claim even (as the " triumph of the means over the end " ) to tell how the world should be managed and what must be its destiny. At the same time, it is suggested that the dominance of " technolanguages " is growing, that the various attempts to overcome this crisis through the use of " artificial intelligence " are extremely promising, provided however that we agree to " a criticism of the strategic time-space ". In the second section, the author deals with the main problems and constraints linked with the conversion of strategic expertise into information processing languages and recommends that research be done along five axes : an update of the " fundamental connectors ", a kind of synapse in the strategic thinking, a study of the " attributes " and a setting up of such elaborate typology as " linguistic atoms ", and finally analyses of " contexts " and " key questions ".